1983
DOI: 10.1111/j.2042-3306.1983.tb01734.x
|View full text |Cite
|
Sign up to set email alerts
|

An energetic basis of equine performance

Abstract: Summary Although different physiological and behavioural attributes are needed for various types of equine competition, successful racing depends primarily on the animal's metabolic ability to convert chemical energy to mechanical energy — the function of muscle. Components of these energetic processes include the rate, efficiency and interaction of aerobic and anaerobic metabolism in muscle and the supply and utilisation of fuel. In anaerobic work like racing, fatigue processes may be largely regarded as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Physical performance results from the conversion of chemical in mechanical energy into the muscle cells [19]. The knowledge of the metabolic pathways during a threeday event is of vital importance, information which can be used as an aid in the planning of training schedules for this competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical performance results from the conversion of chemical in mechanical energy into the muscle cells [19]. The knowledge of the metabolic pathways during a threeday event is of vital importance, information which can be used as an aid in the planning of training schedules for this competition.…”
Section: Discussionmentioning
confidence: 99%
“…Sci. 61(1): [13][14][15][16][17][18][19][20] 1999 pattern of fibre recruitment, muscle fibre composition and contractil and metabolic properties of the muscular fibres [20,25,38]. Even the high velocity exercises performed by Thoroughbred racehorses have a marked dependence on aerobic metabolism, since a high oxygen uptake and an increased red cell volume have been reported [8,25,38].…”
mentioning
confidence: 99%
“…These investigators demonstrated higher plasma LA in faster and better performer horses in distances lesser than 2 000 m. Similarly, in a study in Standardbred trotters with a wide range of racing abilities, blood LA was greater in superior performing horses after races of 2 100 m (Räsänen et al 1995). McMiken (1983) suggested that energy production is predominantly anaerobic for the first 40 to 50 sec (approximate distance of 650 to 800 m for a Thoroughbred), after which time the importance of aerobic energy supplies increase susbstancially. The Andalusian horses of our study covered a total distance near of 5 000 m, and as they depended in a great extent of aerobic metabolism, and hence the inverse relationship between PLA and working capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that inclining the treadmill at a 3.5% slope minimized the differences of the physiological response between track and treadmill conditions; however, locomotion on the treadmill remained different. (Leach and Dagg, 1983;McMiken, 1983;Persson, 1983;Dalin and Jeffcott, 1985; Thornton, 1985). To obtain a comprehensive picture of the interrelationships between variables from different body systems, classical statistical procedures are insufficient to synthesize all the information obtained during a standard exercise test.…”
mentioning
confidence: 99%